(3ZGjI GdfgGjI aj WHbGJ GdbQGA Chdi GdQhGjI hGdOQGjIs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s
(3ChdgG (B:s
(3JHOC HJQLeI CHj Hf cYH s
(3BNQgG (B:s
(3JfJgi HJQLeI GdMSf Hf MeRI Gdeci s
(3GdehLhO efg bWYI JHOC HJQLeI CHj Hf cYHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B292 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B188s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B201 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B222 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3QLGd (B222) s
Keywords: (3GdJGQjNs